An Approach to Good Living and Rural Tourism as Development Alternatives of the Municipality of Cajamarca (Revista Científica Compendium, 2020)
The article aims to present the following aspects: to approach the incidence of the characteristics of good living with respect to Colombian regulations regarding tourism planning and elements of transformation in the development of the tourist undertakings "Urapanes del Bosque" and "Finca la Florida" of the Municipality of Ibagué and Cajamarca of the Department of Tolima. The present study was developed around two types of research, exploratory and descriptive, chosen for the little information regarding the planning and regulations that govern the development of tourist activities in Cajamarca. The results show that Good living and rural tourism generate conditions of justice and equality, the importance of the Nature-Society relationship. Thus, as the emergence of alternatives to development from the local, through the production chain, maintaining its rural identity from the historical context and generating greater participation and democracy regarding the development of the Municipality of Cajamarca.
Keywords: good living; rural tourism; development alternative; democratic tools; territorial planning